Pemanfaatan Remiten Pelaku Mobilitas Internasional Tenaga Kerja Indonesia (Tki)Dan Pengaruhnya Terhadap Pendapatan Total Keluarga (Studi Kasus Desa Munggur, Kecamatan Mojogedang, Kabupaten Karanganyar) - Shidiq, Muhamad; , Drs. Priyono, M. Si (2017)
The purpose of this study were (1) determine the demographic characteristics (age, sex, marital status, number of dependents) and socio-economic (education, employment in the goal area, home ownership, ownership of health insurance, family income) perpetrators of international mobility in the village Munggur , (2) determine the factors that push and pull actors international mobility in the area of research, (3) determine the utilization of the results remitten by perpetrators of migrants in the area of research, and (4) determine the contribution perpetrator (remittance) international mobility of labor migrants to income of families in the area research. The method used in this research is survey method with kuosioner. The results obtained from this study were (1) the demographic, social and economic respondents were as follows: (a) the majority of perpetrators of international mobility of Village Munggur productive age (15-64 years) and perpetrators of most international mobility has a lifespan of 18 - 26 years, ie by 50%, (b) the majority of perpetrators of international mobility of Village munggur gender to male, ie as many as 12 people (75%), (c) the majority of perpetrators of international mobility of Village Munggur marital status which is equal to 68 , 8%, (d) the majority of perpetrators of international mobility of Village Munggur have a number of dependents bit which ranges from 3 - <4, 56%, (e) the majority of perpetrators of international mobility of Village Munggur have a level of secondary education, which is equal to 87 , 5%, (f) the majority of perpetrators of international mobility of Village Munggur have low family income as many as 10 people (62.5%), (g) the majority of perpetrators of international mobility of Village Munggur home ownership status still belongs to the parents as much as 9 people (56.25%), and (h) the majority of perpetrators of international mobility of Village Munggur have JAMKESMAS card as many as 14 people (87.5%), (2) push and pull factors of international mobility actors: (a) a driving factor most perpetrators of international mobility of Village Munggur is low family income, as many as 14 respondents (87.5%) of the total respondents as many as 16 people, and (b) a pull factor for most players on the international mobility Munggur village is salaries height, as many as 15 people (94%) of the 16 respondents, (3) the majority of perpetrators of international mobility purposes of Village Munggur is to Negara Malaysia on the grounds close to the country of origin and language are still allied, as many as 10 people (62.5 %) of the 16 respondents, and (4) the contributions made by the majority of perpetrators of international mobility of Village Munggur to income of the family is large, that is between 26.31% - 32.84% with a total of 12 respondents (75%) of the total 16 respondents.